SYSTEMATIC REVIEW OF MALAYSIAN TASKA: ASSESSING THE MISALIGNMENT BETWEEN TEACHING-LEARNING PRACTICES AND MODERN PARENTAL ASPIRATIONS - NUR ADIBAH MOHD AZLEM; MOHD NAZRI ABDUL RAHMAN (P3I UMSurabaya, 2025)
This paper explores the implementation of teaching and learning (T&L) approaches for infants and toddlers in Malaysian childcare centres (TASKA) and examines how these practices align with the aspirations of modern parents. Using a library research method, the paper reviews theoretical frameworks and literature on early childhood development, highlighting the importance of play-based learning, structured daily routines, sensory play, early communication, and social interaction. Findings indicate that while these approaches contribute to children’s holistic development, challenges such as uneven quality of facilities, limited teacher training, and the cautious integration of technology remain. The review concludes that strengthening professional development, enhancing collaboration with parents, and adopting context-sensitive models are crucial to meeting parental expectations and sustaining quality early childhood education in Malaysia.